Activated Growth Factor (AGF): An Advanced Modality of Platelet-Rich Plasma as a New Biological Agent for the Treatment of Degenerative and Traumatic Conditions - Rachmat Hidayat; Kemas Abdul Mutholib Luthfi; Maria Margareth Wilson; Shina Abdulkadir (Sriwijaya Journal of Internal Medicine, 2025)
Platelet-rich plasma (PRP) has emerged as a promising therapeutic modality for various medical applications, particularly in regenerative medicine and wound healing. This is largely attributed to its rich concentration of growth factors (GFs) that play pivotal roles in tissue repair and regeneration. However, the inherent limitations of PRP, such as the variable GF concentrations and short-lived release kinetics, have spurred the development of advanced modalities to enhance its therapeutic efficacy. Activated growth factor (AGF) represents one such advancement, aiming to optimize the release and bioavailability of GFs from platelets. This comprehensive review delves into the biological mechanisms underlying AGF, its preparation methodologies, preclinical and clinical evidence supporting its use, and its potential applications in treating degenerative and traumatic conditions. Furthermore, it explores the advantages of AGF over conventional PRP and discusses future directions for research and clinical translation.